Proceedings of the 55th Annual Meeting of the Association For Computational Linguistics (Volume 1: Long Papers) 2017
DOI: 10.18653/v1/p17-1035
|View full text |Cite
|
Sign up to set email alerts
|

Learning Cognitive Features from Gaze Data for Sentiment and Sarcasm Classification using Convolutional Neural Network

Abstract: Cognitive NLP systems-i.e., NLP systems that make use of behavioral data -augment traditional text-based features with cognitive features extracted from eye-movement patterns, EEG signals, brain-imaging etc.. Such extraction of features is typically manual. We contend that manual extraction of features may not be the best way to tackle text subtleties that characteristically prevail in complex classification tasks like sentiment analysis and sarcasm detection, and that even the extraction and choice of feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 30 publications
0
54
0
Order By: Relevance
“…They show that fixations not only have an impact in detecting sentiment, but also improve sarcasm detection. They train a convolutional neural network that learns features from both gaze and text and uses them to classify the input text (Mishra et al, 2017a). On a related note, Raudonis et al (2013) developed a emotion recognition system from visual stimulus (not text) and showed that features such as pupil size and motion speed are relevant to accurately detect emotions from eye-tracking data.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…They show that fixations not only have an impact in detecting sentiment, but also improve sarcasm detection. They train a convolutional neural network that learns features from both gaze and text and uses them to classify the input text (Mishra et al, 2017a). On a related note, Raudonis et al (2013) developed a emotion recognition system from visual stimulus (not text) and showed that features such as pupil size and motion speed are relevant to accurately detect emotions from eye-tracking data.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Mishra et al () utilized CNN to automatically extract cognitive features from the eye‐movement (or gaze) data to enrich information for sarcasm detection. Word embeddings are also used for irony recognition in English tweets (Van Hee, Lefever, & Hoste, ) and for controversial words identification in debates (Chen, Lin, & Ku, ).…”
Section: Sarcasm Analysismentioning
confidence: 99%
“…A pooling operation (max, sum, average) can be conducted on the feature map. The classification layer (dense layer) conducts classification that is based on the results from the pooling layer (Mishra, Dey, & Bhattacharyya, 2017). For the CNN-LSTMs, the CNN is used to extract features from the text representation.…”
Section: Stacked Lstmsmentioning
confidence: 99%